2015
DOI: 10.4103/2251-9572.218776
|View full text |Cite
|
Sign up to set email alerts
|

Association between epicardial fat thickness and premature coronary artery disease: A case control study

Abstract: Background:The association between epicardial fat thickness (EFT) and premature coronary artery disease (CAD) has not been elaborately studied. Objectives: In the present study, we sought whether such a relationship between EFT and CAD exists. Patients and Methods: Sixty two consecutive subjects, under 50 years of age, who underwent coronary angiography (CAG) with the aspect of CAD, were included in this case control study. They were divided into two groups of 31 subjects, namely CAD (cases) and non-CAD (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…At present, EAT is an independent risk factor for coronary heart disease, and the thickness of EAT is positively correlated with the severity of coronary artery disease. It has a good application value in the diagnosis of coronary heart disease [Yuan 2014;Faghihi 2015]. This study also confirmed that the thickness of EAT in patients with coronary heart disease was significantly higher than that in the normal control group, and the thickness of EAT was positively correlated with the severity of coronary heart disease.…”
Section: Discussionsupporting
confidence: 72%
“…At present, EAT is an independent risk factor for coronary heart disease, and the thickness of EAT is positively correlated with the severity of coronary artery disease. It has a good application value in the diagnosis of coronary heart disease [Yuan 2014;Faghihi 2015]. This study also confirmed that the thickness of EAT in patients with coronary heart disease was significantly higher than that in the normal control group, and the thickness of EAT was positively correlated with the severity of coronary heart disease.…”
Section: Discussionsupporting
confidence: 72%